PENERAPAN LAYANAN HOME VISIT PEMBELAJARAN PADA MASAPANDEMI COVID-19 DI SDN 13 SUMBER MARGA TELANG DESA SUMBERJAYA KEC. SUMBER MARGA TELANG KAB. BANYUASIN - Fitri Yani; Muhammad Fauzi; Mutia Dewi (PAI RAFAH, 2021)
The covid-19 pandemic in Indonesia has had an impact on all fields, including education. As one of the ways to prevent the spread of civil-19 in the field of education in particular, the Minister of Education and Culture of Indonesia has issued circular letter Number 4 of 2020, regarding the implementation of learning during the covid-19 emergency which explains the learning process that is transferred to home or better known as online learning.The number of problems that arise as a result of online learning so that an offline learning system is implemented in the form of a learning home visit service which is implemented as an effort to solve students’ online learning problems during the current pandemic and continue to provide education directly but still by limiting associations and maintaining health protocols.This research uses qualitative research. With data, collection techniques are done by conducting observations, interviews, and documentation as supporting data. The analysis technique uses a research model from Miles and Huberman, namely data reduction, data presentation, and conclusions.From the results of the study, it can be concluded that: 1) The implementation of the learning home visit service at SDN 13 Sumber Marga Telang went well with several stages, namely the preparation stage, the implementation stage of the learning home visit service, the monitoring and evaluation stage, namely the preparation stage, the implementation stage of the learning home visit service, monitoring and evaluation stage, the follow-up stage and the last one, report stage. 2) Obstacles faced by teachers in implementing learning home visits during the covid-19pandemic at SDN 13 Sumber Marga Telang include obstacles or obstacles in planning, obstacles in implementation, obstacles when monitoring and evaluating, and obstacles when taking action further as well as obstacles in the reporting process.